Revisiting the Single-Case Approach to Studying Reading Disorders. Issue 3 (September 2015) - Inhoff, Albrecht W.; Laszlo, Sarah
<x xml:space="preserve">Abstract</x> Oscar Marin was a neurologist with a remarkably broad interest in the brain and its function. He was passionate about understanding how the brain processes language and about helping people with acquired language disorders through his science-based practice. Here we honor his memory by presenting a review and commentary charting the cycle of neuroscientific approaches to studying reading disorders over the past century. During this time, "best practices" have changed from individual case studies to group studies and mega-studies and back again to individual studies. We show how, across decades and almost unimaginable advances in neuroimaging technology, the individual approach taken by Oscar Marin has retained its importance.